Parallel, Washington County - Messer, Keegan (Kansas State University, The Chapman Center for Rural Studies, 2016)
The town of Parallel existed in Lincoln Township, Washington County, Kansas. Its unique geography included being located along the border between Washington and Riley County. The town officially existed until 1905 but continued to have residents until at least the 1950s. To create this sketch of Parallel, the author used business records, on-site photography, and research at Washington County Historical Society.
Keegan Messer, “Parallel, Washington County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/178.
Keywords: Washington County; Parallel; Riley County; Waterville Fancy Creek Evangelical United Brethren Church; Lincoln Township; Mayday Township